Korelasi Profil Darah Dengan CRP Serum pada Pasien Diabetes Mellitus dengan Ulkus Diabetikum - Andika Aliviameita; Puspitasari Puspitasari; Yanik Purwanti (THE JOURNAL OF MUHAMMADIYAH MEDICAL LABORATORY TECHNOLOGIST, 2021)
Diabetes mellitus is a metabolic disorder that experiences hyperglycemia and causes various complications, including diabetic foot ulcers (DFU). Hyperglycemia can cause chronic inflammation and decreased function of immune cells. This study aims to determine the correlation between blood profiles and serum C-Reactive Protein (CRP) in diabetes mellitus patients with diabetic ulcers. A total of 30 blood samples of diabetes mellitus patients with blood tests and serum CRP. Blood profile examination used an automatic method with a hematology analyzer, erythrocyte sedimentation rate (ESR) using the Westergreen method, and serum CRP using a semi-quantitative method. In the  correlation regression multiple test knowed that the parameters associated with CRP serum are hemoglobin (r = 23.553; p = 0.015), hematocrit (r = -8.678; p = 0.016), leukocyte count (r = 2.098; p = 0.004), and platelet count (r = -0.112; p = 0.002) because it has significance (p < 0.05). Meanwhile, the parameters of erythrocyte count (r = -8.717; p = 0.359), and ESR (r = -0.142; p = 0.109) had no effect on serum CRP levels because they had significance (p> 0.05). The conclusion of this study shows there is a strong correlation (r = 0.777) between blood profile and serum CRP in diabetes mellitus patients with diabetic foot ulcers.